PHEV Charging Strategy Via User Preferences and its Impacts on Power System Network - Mohd Redzuan, Ahmad; Ismail, Musirin; Muhammad Murtadha, Othman; Nur Azzammudin, Rahmat (2014)
Uncontrolled PHEVs charging will cause severe impacts on a power system network, especially on the distribution system; i.e. feeders, cables and transformers overload hence shortened its life. In this paper, PHEV charging strategy namely SOC-based charging has been proposed. This charging strategy focused on user needs, i.e. full charged the battery within plugged-in time frame considering maximum charging rate from the standard outlet. Moreover, it will reduce the peak loads as well as improving the load factor on a power system network. Real vehicle travel data from National Household Travel Survey (NHTS) is used to represent PHEV types, miles driven and its final arriving times. This proposed technique also comprehensively used to present the impact of charging PHEV on power system networks considering PHEV battery sizes and maximum charging levels. Vehicles Charging Load Profile (VCLP) is developed and implemented in IEEE 30-bus test system that represents a portion of American Electric Power System (Midwestern US). Normalization technique is used to represent real time loads of IEEE 30-bus test system.Comparative study has been performed with respect to uncontrolled charging technique. Results indicated that the proposed charging strategy not only achieved the required battery capacity but also has improved peak load and load factor thus reduces impacts on power system networks.